ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT. SINAR BINTANG MANDIRI MEDAN - Silalahi, Magdalena; Sitanggang, Darna; Sihombing, Sarimonang (UNIKA Santo Thomas, 2022)
PT Sinar Bintang Mandiri is a company engaged in the procurement of goods, and mechanical and electrical services serving medium and large companies, both private and government. This study discusses improving employee performance which is influenced by various factors. Factors that affect performance are stress level, compensation system, job design, effectiveness and efficiency, initiative, ability and expertise, knowledge, personality, work motivation, job satisfaction, work environment, leadership style, organizational culture, commitment, and work discipline. The purpose of this study was to determine the factors that affect employee performance at PT. Sinar Bintang Mandiri Medan. The population in this study were employees of PT. Sinar Bintang Mandiri Medan, which is in the field of providing services for technicians and mechanical helpers, totaling 75 people. This study uses primary data by distributing questionnaires. The sample used in this study were all employees of PT. Sinar Bintang Mandiri Medan for technicians and mechanical helpers. The analysis technique used is factor analysis. The analysis was carried out using the SPSS version 22 program. From the 15 variables formed 5 factors that affect the performance of employees at PT. Sinar Bintang Mandiri Medan. The results of this study indicate that the dominant factor affecting the performance of employees at PT. Sinar Bintang Mandiri Medan is a job design factor that has a correlation value of 0.768, the ability and expertise factor has a correlation value of (0.816), the personality factor has a correlation value (0.821), job satisfaction has a correlation value (0.805), organizational culture has a correlation value (0.816).